Physiological and anthropometric characteristics of starters and non-starters in junior rugby league players, aged 13-17 years - Gabbett, T. J. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: The purpose of this study was to investigate the physical qualities of junior rugby league players (Under 14, 16, and 18) and determine if preseason fitness measures were significantly different for the players selected to play in the first competitive game of the season (i.e. starters) compared to the players not selected (i.e. non-starters). METHODS: Eighty-eight junior (N.=53 Under 14; N.=20 Under 16; N.=15 Under 18) subelite rugby league players participated in this study. All players were registered with the same junior recreational rugby league club. Subjects underwent measurements of anthropometry (height, body mass, and sum of four skinfolds), speed (10-m, 20-m, and 40-m sprint), change of direction speed (505 test), estimated lower body power (vertical jump), and estimated maximal aerobic power (multi-stage fitness test) at the beginning of the competitive season. RESULTS: While the relative importance of the different physical qualities differed between playing levels, starters tended to be taller, have faster change of direction speed, and greater playing experience than non-starters. Moderate to large effect size differences were detected between starters and non-starters for speed and estimated maximal aerobic power results. CONCLUSIONS: These findings demonstrate that junior rugby league players selected to the starting team have better developed physical qualities than non-starting players. Coaches should emphasise the development of speed, change of direction speed, and aerobic qualities in junior rugby league players.